Improved direct control of single stage photovoltaic powred system - Chouaib, Rahli; Ouada, Mehdi; Ryad, Mebarek Abdesslam; Saad, Salah (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This paper introduces a novel direct control quasi-Z-source inverter (qZSI) topology as a viable alternative to conventional two-stage converters in photovoltaic (PV) systems. The proposed control strategy effectively merges duty cycle and modulation index within a space vector pulse width modulation (SVPWM) framework for both DC and AC control. To assess the system’s performance under diverse weather conditions, the INC and P&O maximum power point tracking maximum power point tracking (MPPT) algorithms are employed. Rigorous simulations conducted using MATLAB/Simulink demonstrate the proposed method’s ability to achieve multi-objective optimization of PV systems, enhancing overall system efficiency and reliability.